2014
DOI: 10.1371/journal.pntd.0002912
|View full text |Cite
|
Sign up to set email alerts
|

Blood Drain: Soil-Transmitted Helminths and Anemia in Pregnant Women

Abstract: The main cause of anemia is iron deficiency, which, in turn, can result from a wide range of factors. Iron intake may be insufficient because of a low dietary iron content, less bioavailable (i.e., non-heme) iron, or because of poor absorption of iron due to concurrent ingestion of inhibitors such as cereals and grain. In addition, iron may be lost because of infection by parasites that destroy red blood cells, such as malaria-causing Plasmodium species, or by blood-feeding parasites, such as the soil-transmit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 25 publications
2
33
1
Order By: Relevance
“…Previous studies from Uganda, Nigeria and Nepal found no such significant association between parasitic infections and IDA [51][52][53]. Similarly, a recent study concluded that the association between anemia and trichuriasis is less clear [54]. Moreover, we found no significant associations between IDA and hookworm infections and schistosomiasis among these subjects.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous studies from Uganda, Nigeria and Nepal found no such significant association between parasitic infections and IDA [51][52][53]. Similarly, a recent study concluded that the association between anemia and trichuriasis is less clear [54]. Moreover, we found no significant associations between IDA and hookworm infections and schistosomiasis among these subjects.…”
Section: Discussioncontrasting
confidence: 74%
“…), Ascaris lumbricoides, and Trichuris trichiura, represent a leading global cause of anemia, malnutrition, and growth delay, especially among children and women of childbearing age. [1][2][3][4] Together, these three intestinal nematodes infect more than 1 billion people worldwide, with twice that number currently living in endemic areas. Among the STHs, hookworms are associated with a significant burden of disease, which is primarily attributable to gastrointestinal blood loss caused by adult worms that attach to the intestinal mucosa and feed on blood from lacerated capillaries.…”
Section: Introductionmentioning
confidence: 99%
“…Women of reproductive age (WRA) in low-and middle-income countries are particularly vulnerable to morbidity resulting from soil-transmitted helminth infection (STH) [1][2][3]. It has recently been estimated that approximately 700 million WRA in over 100 countries are at risk of morbidity from these infections [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Most previous research on STH infections and deworming has focused on children. Even though it is well known that worm infections cause and exacerbate anemia during the different stages of a woman's reproductive life span, WRA have been under-studied in this context [2,11]. The resulting lack of uptake by endemic countries of deworming programs that include women of reproductive age inadvertently neglects an important cause of STH-attributable morbidity and reinforces gender inequities [3,5,12].…”
Section: Introductionmentioning
confidence: 99%